BIMBINGAN KARIR UNTUK MENUMBUHKAN ETOS KERJA ISLAMI SANTRI - Mahmudah; Khaudli, Muhammad Imam; Amalia, Zahrotul (JKaKa:Jurnal Komunikasi dan Konseling Islam, 2025)
Career guidance is a part of the need to foster the work ethic of Islamic students at the Mukhtar Syafa'at Blokagung Banyuwangi Islamic Boarding School. The purpose of this study is to analyze the implementation and supporting factors and inhibitors of career guidance in fostering the work ethic of students at the Mukhtar Syafa'at Blokagung Banyuwangi Job Training Center. The research method uses a qualitative approach, with data collection techniques through observation, interviews, and documentation. Data analysis uses the Miles and Huberman interactive model consisting of data reduction (data reduction), data display (data presentation) and drawing conclusions/verification and drawing conclusions. The results of this study indicate that career guidance in fostering the work ethic of Islamic students is carried out in the form of work practices and worship. One of the strategies provided by career guidance is to involve students in the work training body, as well as preparing production facilities and infrastructure. The existence of the work training agency is able to foster a work ethic in students, so that students know that Islamic work ethic is a belief of a Muslim, that work is related to the purpose of his life, namely trying to obtain Allah's pleasure through work or good deeds